Explorations: Stars, Galaxies, and Planets - T.Arny Thomas (MC Graw Hill, 2002)
Now one of the best selling Astronomy textbooks is available in a "stars-first" organization. The same great writing style, the same great pedagogical tools helping students through concepts as well as the same complete technology package is available (CD-ROM, Website, PowerWeb and NetTutor)! --This text refers to the CD-ROM edition.